2020
DOI: 10.1111/ajad.13004
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Reactivity Moderates the Indirect Link Between Child Maltreatment and Young Adult Alcohol Use Problems Via Depressive Symptoms

Abstract: Background and Objectives Young adults with childhood maltreatment (CM) histories are particularly vulnerable to depressive symptoms and alcohol use problems. Research suggests that maltreated youth may misuse alcohol in part to alleviate depressive symptoms. However, many youths with depressive symptoms exercise self‐control and abstain from heavy alcohol use. The present study aimed to examine the influence of heart rate variability reactivity (HRV‐R), a psychophysiological biomarker of self‐regulation, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(78 reference statements)
1
5
0
Order By: Relevance
“…Studies have shown that substance misuse elicits numerous adverse effects on the brain [3], autonomic nervous system [4], cardiovascular function [5], and sleep quality of individuals [6]. In terms of the autonomic nervous system, substance misuse exhibits numerous significant differences in physiological parameters compared with nonusers [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that substance misuse elicits numerous adverse effects on the brain [3], autonomic nervous system [4], cardiovascular function [5], and sleep quality of individuals [6]. In terms of the autonomic nervous system, substance misuse exhibits numerous significant differences in physiological parameters compared with nonusers [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with ACEs were more likely to use or abuse alcohol or other substances during early adulthood; this association was pronounced for multiple ACEs. 5,6,99-147 Interestingly, Crandall et al 99 showed that when counter-ACEs were included in the model, they weakened the significant association of ACEs with substance use. This suggests that positive and encouraging childhood experiences can not only “cancel out” the effect of adverse experiences but also serve as a protective factor against substance use in early adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…Further, there is a disparity in access to mental health services to improve behavioral health outcomes in rural populations (Ziller & Coburn, 2018 ). Liu et al ( 2020 ) specifically highlighted the rationale for studying alcohol use problems in a rural sample was to inform prevention and intervention programs targeting rural young adults. Similarly, Murry and colleagues ( 2013 ; 2014 ) described the need to apply findings to address HIV/AIDS disparities among African American males in the rural south.…”
Section: Resultsmentioning
confidence: 99%
“…At the microsystem level, process variables like Adverse Childhood Experiences (ACEs) and child-maltreatment appear to be more prevalent in rural communities (Sedlak et al, 2010 ; Crouch et al, 2019 ), which was specifically cited as a reason for selecting a rural sample to study how this impacted rural young adult development (Liu et al, 2020 ). Carrillo ( 2016 ) cited the lack of Latinx representation in rural teachers in primary and secondary education as a barrier to feeling at “home” in the new Latin south.…”
Section: Resultsmentioning
confidence: 99%